H.R. 4497 A BILL (Tufts Archival Research Center, 2007)
Proposed House of Representatives’ bill H.R.4497 concerning fire safety and cigarettes. Includes endorsement by several fire safety groups. Reestablishes the Interagency Committee on Cigarette and Little Cigar Fire Safety first created in 1984. Outlines make-up of committee including scientists in various disciplines and their responsibilities in terms of investigation into the fire safety of cigarettes.